2018
DOI: 10.3791/56866
|View full text |Cite
|
Sign up to set email alerts
|

Fabricating Optical-quality Glass Surfaces to Study Macrophage Fusion

Abstract: Visualizing the formation of multinucleated giant cells (MGCs) from living specimens has been challenging due to the fact that most live imaging techniques require propagation of light through glass, but on glass macrophage fusion is a rare event. This protocol presents the fabrication of several optical-quality glass surfaces where adsorption of compounds containing long-chain hydrocarbons transforms glass into a fusogenic surface. First, preparation of clean glass surfaces as starting material for surface mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…We recently developed optical-quality glass surfaces that enabled the first time resolved views of IL-4-induced macrophage fusion and MGC formation (Faust et al, 2017;Faust et al, 2018). Using these surfaces, we showed that macrophage fusion occurred between the intercellular margins of macrophages.…”
Section: Phase-dense Protrusions At the Leading Edge Precede Macrophamentioning
confidence: 99%
See 1 more Smart Citation
“…We recently developed optical-quality glass surfaces that enabled the first time resolved views of IL-4-induced macrophage fusion and MGC formation (Faust et al, 2017;Faust et al, 2018). Using these surfaces, we showed that macrophage fusion occurred between the intercellular margins of macrophages.…”
Section: Phase-dense Protrusions At the Leading Edge Precede Macrophamentioning
confidence: 99%
“…The system was configured and operated as previously described (Chen et al, 2014). Briefly, eGFP-LifeAct and/or mRFP-LifeAct peritoneal macrophages were applied to 5-mm cover glass surfaces adsorbed with long-chain hydrocarbons (Faust et al, 2017;Faust et al, 2018). IL-4 (10 ng/mL) was added and LLSM was conducted 8-10 hours thereafter.…”
Section: Lattice Light Sheet Microscopymentioning
confidence: 99%
“…Since PCTFE plastic is not amenable to most imaging techniques, we took advantage of recently developed optical-quality glass surfaces prepared by adsorption of long-chain hydrocarbons such as paraffin that promote high levels of macrophage fusion ( Faust et al. , 2017 , 2018 ).In this series of experiments, rather than macrophage cell lines, we used primary macrophages isolated from the inflamed mouse peritoneum ( Helming and Gordon, 2007a ; Podolnikova et al. , 2016 ; Faust et al.…”
Section: Resultsmentioning
confidence: 99%
“…, 2019 ). Briefly, peritoneal cells (5 × 10 6 cells/ml) in Hank’s balanced salt solution (HBSS; Cellgro, Manassas, VA) supplemented with 0.1% bovine serum albumin were applied to acid-cleaned or paraffin-coated glass coverslips (prepared as described by Faust et al., 2017 , 2018 ). Cells were incubated in 5% CO 2 at 37°C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…To investigate the mechanism of ZLS formation, we established an in vitro system that allowed us to generate ZLSs reproducibly. Since PTFE plastic is not amenable to most imaging techniques, we took advantage of recently developed optical-quality glass surfaces prepared by adsorption of longchain hydrocarbons such as paraffin that promote high level of macrophage fusion (Faust et al, 2017;Faust et al, 2018). In this series of experiments, rather than macrophage cell lines, we used primary macrophages isolated from inflamed mouse peritonea (Helming and Gordon, 2007a;Podolnikova et al, 2016;Faust et al, 2019) to avoid the robust proliferation observed in the cultures of macrophage cell lines.…”
Section: Formation Of Zlss In Vitromentioning
confidence: 99%